Improving Allocative Efficiency of the HIV Response in Kenya : A Country-Level Analysis Using the Optima HIV Model - Lukoba, Benard; Simiyu, Joseph; Chege, Wendy; Kelly, Sherrie; Minnery, Mark; Sithole, Lonjezo; Shubber, Zara (World Bank, Washington, DC, 2021)
This report summarizes findings of an HIV allocative efficiency study conducted in Kenya between 2018 and 2020. The study was commissioned to contribute to the evidence base for strategic planning processes at national and county level. This report documents the epidemiological impact of 2014/15–2018/19 Kenya AIDS Strategic Framework (KASF-I) and presents estimates of the optimized annual resource allocations within all 47 counties for the period between 2019 and 2030 to minimize new HIV infections and HIV-related deaths by 2030 for varying budget levels. The report also presents estimated outcomes for infections and deaths by 2025 to align with the end of the new 2020/21–2024/25 KASF-II and examines the future trajectory of the epidemic at national and county levels.